(untitled) (Research, Society and Development, 2022)
Health planning has been carried out in Brazil after the implementation of the Unified Health System. However, health plans are often not easily envisioned and are therefore little known. The concept map is a graphical tool that organizes and represents knowledge. The objective of this study was to use the conceptual map as a strategy for the critical visualization of a State Health Plan. Therefore, documental research with a qualitative approach was carried out, initially delimiting the state of the art of the subject through a literature review and then the documentary research was carried out, whose information was collected from the State Health Plan of Alagoas - PES 2016-2019 and finally, the research result was presented through conceptual maps permeated by the discussion. After analyzing the document, its structure and commitments signed for the 2016-2019 quadrennium were identified, which were arranged in conceptual maps, with the axes, guidelines, and objectives. The graphic demonstration of the plan through concept maps proved to be consistent to facilitate those interested in understanding the guidelines that should give rise to initiatives in the field of health, being considered a relevant proposal.